CONTRIBUTIONS OF MAHMUD YUNUS TO THE INTERPRETATION OF THE QURAN: A STUDY OF TAFSIR QUR’AN KARIM - Ahmad, Khadher; Marardi, Khairuddin (Online Journal of Research in Islamic Studies, 2017)
Mahmud Yunus was a scholar in the field of Quranic translation. His book, Tafsir Qur?an Karim, was a simple translation reference book first written in the modern Malay era and is widely used until today. This article is meant to highlight his ability against his background and his effort in writing the book. His simple yet robust approach with translation notes and explanations in the footnotes, made his approach different from others. However, he still practiced the same translation methods as that of other translation scholars. Analysis shows that Mahmud Yunus applied eight methods in his translation works: translation from one Quranic verse to another, translation of Quranic verses against supporting Hadith, translation of Quranic verses based on opinions of the companions of Prophet Muhammad (p.b.u.h.), translation of Quranic verses based on the opinion of tabi?in, translation of Quranic verses based on logical thinking, translation of Quranic verses based on their meaning, presentation of proverbial sayings, and interpretation through stories.